2004
DOI: 10.4141/p03-208
|View full text |Cite
|
Sign up to set email alerts
|

Barley dry matter yield, crop uptake, and soil nutrients under fresh and composted manure containing straw or wood-chip bedding

Abstract: . 2004. Barley dry matter yield, crop uptake, and soil nutrients under fresh and composted manure containing straw or wood-chip bedding. Can. J. Plant. Sci. 84: 987-999. Limited information exists on the effect of fresh versus composted beef cattle manure containing straw or wood chips on barley (Hordeum vulgare) yield, nutrient uptake, and soil nutrient status in the Great Plains region of North America. Barley was grown on an irrigated clay loam soil in southern Alberta from 1999 to 2001. The treatments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 22 publications
(31 reference statements)
0
34
1
Order By: Relevance
“…4a). Barley dry matter yield increased from 1999 to 2001 at the 13 and 39 Mg ha -1 rates (Miller et al 2004), but at the 77 Mg ha -1 rate, DM yield increased from 1999 to 2000, and then decreased slightly in 2001. Barley is salt tolerant and yield reductions do not occur until EC > 8.0 dS m -1 , whereas other crops such as corn, timothy hay (Phleum protense L.), peas (Pisum sativum L.), and field beans (Phaseolus vulgaris L.) have a low tolerance of soil salinity with yield reductions occurring when the EC > 4.0 dS m -1 (McKenzie 1988).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…4a). Barley dry matter yield increased from 1999 to 2001 at the 13 and 39 Mg ha -1 rates (Miller et al 2004), but at the 77 Mg ha -1 rate, DM yield increased from 1999 to 2000, and then decreased slightly in 2001. Barley is salt tolerant and yield reductions do not occur until EC > 8.0 dS m -1 , whereas other crops such as corn, timothy hay (Phleum protense L.), peas (Pisum sativum L.), and field beans (Phaseolus vulgaris L.) have a low tolerance of soil salinity with yield reductions occurring when the EC > 4.0 dS m -1 (McKenzie 1988).…”
Section: Discussionmentioning
confidence: 96%
“…Rainfall during the time that the barley crop was growing (May-Aug.) in 1999 was slightly greater (110%) than the long-term average (Miller et al 2004). Most (57%) of the rainfall in 1999 occurred in June and July.…”
Section: Rainfall and Irrigationmentioning
confidence: 87%
See 2 more Smart Citations
“…Miller et al (2004) reported that SIN was 62 to 199% greater for beef FM than CM after 2 and 3 yr of manure application for a clay loam soil in southern Alberta.…”
mentioning
confidence: 99%